Potential of plant tonic on controlling fusarium oxysporum f.sp. cubense, the causal agent of banana wilt - Roshaidi, Nur Farzana (2017)
Fusarium wilt caused by the soil inhabiting fungus, Fusarium oxysporium f.sp. cubense is a major factor limiting commercial banana production in Malaysia. Control measures involving field sanitation, soil fumigation, organic amendments and crop rotation are generally non-effective. The effective method of controlling fusarium wilt is the planting of new resistant varieties however, it is not only time consuming but is at time not feasible as this pathogen can overcome resistant, and there is no resistant cultivars that has been developed in Malaysia. Biopesticide control is the best alternative method to control the Fusarium wilt as it is not only environmentally friendly but are less expensive. One such biopesticides is the use of plant tonic which has fatty acids as the active ingredient. It has been used to control several diseases on crops by inhibiting the growth of fungi, bacteria and virus. The medium chain fatty acids such as Lauric acid, Capric acid and Palmitic acids has been reported to inhibit fungal, bacterial and viral infection. Related study on the use of plant tonic crop diseases has not been reported, thus the objectives of this study is to determine the potential use of plant tonic to control fusarium wilt of banana caused by Foc. Foc was cultured in PDA containing five different treatments which control, 1 ml, 2 ml, 3 ml and 4 ml. The experiments were focused on mycelial growth of Foc from day 1 until day 7, observed and calculated the spore germination of Foc. After day 7, the plates were left for another 7 days for further incubation and spore count was observed, recorded and calculated. As a result, the activities of plant tonic on mycelial growth was inhibited 40.27% ( 4 ml concentration of plant tonic) as calculated in PIRG and the mycelial growth was 20.30 mm (4 ml ). The spore count of Foc in 4 ml concentration was the least (17.7 x 10^6 spore/ml) and the spore germination of Foc contained 4 ml plant tonic was (5.8 %) which is the least spore germination. Therefore, 4 ml of concentration of plant tonic was the most inhibited the growth of Foc.